Linguistic Revitalization in the Age of Globalization: An Ethnolinguistic Study of the Osing-Speaking Community in Banyuwangi, Indonesia - Prawira, Sophian Djaka; Khadafi, Rozy; Danugroho, Agus (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study explores the processes and challenges of linguistic revitalization within the Osing-speaking community in Banyuwangi, Indonesia, in the context of rapid globalization and cultural homogenization. Employing an ethnolinguistic approach, this research combines participant observation, in-depth interviews, and analysis of local cultural practices to examine how language functions as a marker of ethnic identity and cultural continuity. The findings reveal that globalization exerts a dual influence: it contributes to language shift through the dominance of Indonesian and global media, yet simultaneously creates opportunities for revitalization via tourism, cultural festivals, and digital platforms. Community-driven initiatives such as integrating Osing into school curricula, promoting Osing-language performances, and documenting oral traditions, play a central role in preserving linguistic heritage. However, these efforts face structural challenges, including limited institutional support, intergenerational language gaps, and the commodification of culture that risks reducing the language to a symbolic artifact. This study underscores the importance of collaborative strategies involving local communities, educational institutions, and policy-makers to sustain Osing as a living language, offering broader insights into the dynamics of minority language revitalization in the Global South.